(untitled) (Grande Medical Journal, 2025)
Background Blood transfusion is an essential therapeutic intervention in modern medicine, crucial for managing anemia, bleeding disorders, trauma, and perioperative blood loss. Despite its life-saving potential, inappropriate transfusion practices can deplete limited blood resources and increase patient risk. Systematic evaluation of transfusion patterns is necessary to promote judicious use and enhance patient safety. Method A retrospective observational study was conducted over six months (June to December 2024), including all patients who received blood component transfusions. Data were extracted from blood bank records and patient charts, capturing demographics, type and indication of blood component transfused, and requesting department. Descriptive statistics summarized utilization patterns and departmental distribution. Result A total of 1,850 transfusion events involving 3,032 blood components were analyzed. Packed Red Blood Cells (PRBCs) were the most frequently transfused component (1,500 units, 50%), primarily for anemia, surgical support, and critical care. Platelets accounted for 750 units (25%), mainly for thrombocytopenia, gynecological procedures, and critical care. Fresh Frozen Plasma (FFP) comprised 600 units (20%), used for coagulation disorders, major surgeries, and dialysis. Cryoprecipitate was least utilized (150 units, 5%), primarily for hemophilia A and fibrinogen deficiency. Department wise, dialysis had the highest transfusion demand (50%), followed by the intensive care unit (22%) and orthopedic surgery (12%). Lower utilization was observed in gastroenterology, gynecology, internal medicine, pulmonology, and pediatrics. Out of total component requested only 61% percent is transfused. Conclusion PRBCs remain the cornerstone of transfusion therapy, with significant variation in component use across hospital departments. The findings underscore the importance of tailored transfusion strategies and resource allocation, particularly in high-demand areas such as dialysis and critical care. Ongoing evaluation of transfusion appropriateness and outcomes is recommended to further enhance transfusion safety and efficiency.